The Characteristics of Pesantren in the Development of Islamic Education in West Sumatra - Zulmuqim Zulmuqim; Zainimal Zainimal; Martin Kustati; Besral Besral; Refinaldi Refinaldi; Adriantoni Adriantoni (Universitas Islam Negeri Mataram, 2020)
The aim of the study is to investigate the characteristics of pesantren in the development of Islamic education in West Sumatra. This region is well known for the early history of Islamic education in Indonesia. This is a qualitative study where the data were gathered through observation, interview, focus group discussion, and documentation in eleven pesantrens in the province of West Sumatra. This study reveals three main characters of the Islamic boarding schools, namely institutional system, curriculum and learning system and typology. Institutionally, Islamic boarding schools is under the auspices of a foundation. However, leadership and regeneration are still closely linked to the family of the pesantren founders. The curriculum and learning system are integrated from general/state school curriculum, classical pesantren curriculum, and modern Islamic school curriculum. Various classical-medieval literature in Islamic studies, commonly known as kitab kuning, are to a great extent also still used, especially in the institutions that only run traditional Islamic boarding schools (pesantren salaf). Keywords: Characteristics, Islamic boarding schools, Islamic education